The Effect of Rare Earth Y on the Microstructure and Mechanical Properties of an As-Cast Body-Centered Cubic Mg-11Li-6Zn Alloy - Honghui Lin; Xuetao Ke; Guangxin Xiong; Binqing Shi; Zhengrong Zhang; Chuanqiang Li (Metals)
The body-centered cubic (BCC)-structured magnesium–lithium (Mg-Li) alloy is the lightest metal material, but its mechanical properties are poor, especially its strength. In this study, the effect of adding rare earth Y on the microstructure and mechanical properties of as-cast BCC Mg-11Li-6Zn-xY (x = 0, 0.5, 1.2, and 2, in wt.%) alloys was investigated. The results revealed that massive amounts of nano-scale θ (MgLiZn) and/or θ’ (MgLi2Zn) precipitated inside the grains, and some θ phases precipitated at the grain boundaries in the Mg-11Li-6Zn alloy. With the addition of Y, W phases formed at the grain boundary, their content gradually increased with the Y concentration, and the grain size decreased simultaneously. The Mg-11Li-6Zn-0.5Y alloy exhibited higher ultimate tensile strength (190 MPa) and elongation (27%) at room temperature than those (170 MPa and 22%) of the Mg-11Li-6Zn alloy, presenting improvements of 11.8% and 22.7% in strength and ductility, respectively. The improvements in the mechanical properties of the Mg-11Li-6Zn alloy achieved by adding less Y could be attributed to the formation of moderate W phases and a reduction in grain size. However, once the addition of Y became excessive, the mechanical properties of the Mg-11Li-6Zn-1.2Y alloy were reduced due to the formation of too many reticular W phases. In addition, the Mg-11Li-6Zn-2Y alloy containing the highest Y content had the lowest ultimate tensile strength, 163 MPa, and highest ductility, 38%, due to the combined effect of the most reticular W phases and the smallest grains. Furthermore, the fracture morphology of the Mg-11Li-6Zn alloy displayed apparent necking, which became insignificant after the addition of Y, indicating that this addition could improve its uniform plastic deformation ability.